Neo-Victorian Orientations towards the Fictional Writer: Jane Harris’s - The Observations - Arias-Doblas, María Rosario (My University, 2019)
Jane Harris’s The Observations (2007) narrates the story of Bessy Buckley, an Irish girl who searches for work and finds it in Castle Haivers, employed by Arabella. While learning how to become a maid-of-all work, she is asked to keep a record of her daily activities by her mistress. This mystery is solved when Bessy discovers Arabella’s “The Observations”, her own record of the maids’ progression at home, an experiment she conducts for her to find out the distinctive features of the perfect maid. However, the novel unfolds an expected course of actions, which will shift Bessy’s position from being a vulnerable subject to a resilient one, precisely by the writing her story. In this paper I will focus on the character of Bessy, a maid who finds redemption and improvement through friendship, bonding and care, and who pens her story, thus becoming a writer. The act of writing is then coupled with ethics of care, which underlines issues of vulnerability and resilience in a Victorian context through a contemporary lens.
https://www.canal-u.tv/video/la_forge_numerique/neo_victorian_orientations_towards_the_fictional_writer_jane_harris_s_the_observations.53221
Keywords: Literatura inglesa - 2007; Neo-Victorian; Contemporary Fiction; Jane Harris